(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2018)
Acha (Digitaria exilis Kipps. and D. iburua Stapf.) are valuable indigenous food crops in West Africa, but despite several economic potentials of this crop, little or no attention is paid to its germplasm evaluation and improvement. In this study, we assessed genetic diversity and relationship among genotypes of cultivated acha in Nigeria using Inter-Simple Sequence Repeat (ISSR) markers for the first time. Genomic DNA were extracted from the genotypes and we performed fragment amplification by Polymerase Chain Reaction (PCR). A total of 95 loci consisting of 790 bands were amplified by 13 ISSR primers, out of which 53.37% were polymorphic. Loci amplification per primer ranged from 5-10, with an average of 7.30 loci per primer. Eight of the primers had above 50% polymorphism. Cluster analysis separated the genotypes into two major groups; a group consisting of two D. exilis genotypes and the other comprising a mixture of genotypes. The D. exilis in the latter group were distant members and was only similar at 0.72 similarity index. The polymorphism we obtained in the present study showed that the ISSR markers are effective for assessment of genetic diversity of the genotypes. Clustering of D. exilis and D. iburua together suggests a common progenitor but could have been separated by geographical isolation mechanism